Multimodal imaging of bilateral immunogammopathy maculopathy associated to Waldenström's macroglobulinemia. Issue 1 (January 2023) - Bouraoui, Rim; El Matri, Khaled; Falfoul, Yousra; Fakhfakh, Dalel; Mghaieth, Fatma; Chebil, Ahmed; El Matri, Leila
Aim: Our aim is to report a case with bilateral Waldenström's macroglobulinemia (WM) associated maculopathy, assessed with multimodal imaging including swept source optical coherence tomography (SS-OCT) and OCT-Angiography (OCT-A). Methods: Observational case report. Case presentation: A 61-year-old diabetic woman with history of treated WM currently in remission, presented with progressive bilateral visual loss. Best-corrected visual acuity was 20/100 in the right eye (RE) and 20/200 in the left eye (LE). Fundus examination showed bilateral microaneurysms and retinal punctuate hemorrhages and a large macular serous detachment in the LE. There was no retinal ischemia on FA nor macular dye leakage. SS-OCT showed a significant schisis-like intraretinal fluid accumulation in the RE and a large prominent macular detachment with significant subretinal fluid accumulation in the LE. Retinal and choriocapillaris vascular densities were normal on OCT-A. Conclusion: Our case illustrated characteristic multimodal imaging findings in WM associated maculopathy such as schisis-like intraretinal fluid accumulation and angiographically silent serous macular detachment. OCT-A could non-invasively analyze macular vascular densities layer-by-layer, without noticing any vascular anomaly.